The microstructure of high manganese TWIP steels produced via simulated direct strip casting. Issue 1 (2nd January 2022) - Othman, Raudhah; Dorin, Thomas; Stanford, Nikki; Hodgson, Peter
Abstract : Three TWIP steels based on the composition Fe-23Mn-3Si-3.3Al with different carbon concentrations were examined. The alloys were produced by rapid solidification in an experimental apparatus designed to simulate direct strip casting conditions. Examination of the driving force for solidification for this alloy showed the preference for BCC and FCC solidification were very close for this composition, within 10% of one another. This factor combined with the high undercooling resulted in the change in the primary solidified phase. Chemical analysis of the as-cast strip showed inter-dendritic segregation of Si and Al, but negligible segregation of Mn. A simple heat treatment was sufficient to chemically homogenise all alloys and produce microstructures comprising a fully austenitic structure, consistent with thermodynamic predictions.